Synergistic alkaline etching and nitrogen lattice occupation strategy enables gradient defluorinated cathode for high-performance Li/CFx batteries - Hongwei Cai; Xiaoxiao Pan; Cong Li; Hao Luo; Menghan Lin; Mingyi Shang; Jiqiong Lian; Yanan Fu; Hongjun Yue; Huixin Chen; Xiaolong Li; Yujin Tong; et al. (Chemical Engineering Journal, 2026)

Growth-mode-independent glutamine/glutamate/aspartate metabolic shift and urea cycle remodeling driven by FOXA1 in benzo[a]pyrene-transformed human bronchial epithelial cells - Yujin Fu; Yanmin Qi; Yunkun Xing; Yitong Lin; Zhiyu Liu; Juanling Fu; Biyun Yao; Peng Zhao (Toxicology and Applied Pharmacology, 2026)

Retraction notice to “Recent progresses, challenges, and opportunities of carbon-based materials applied in heavy metal polluted soil remediation” [Sci. Total Environ. 856 (2023) 158810] - Tianhong Fu; Baige Zhang; Xing Gao; Shihao Cui; Chung-Yu Guan; Yujin Zhang; Bangxi Zhang; Yutao Peng (Science of The Total Environment, 2026)

Ecological risk transmission network and its response characteristic in heavy metal-contaminated soil ecosystem under different scenarios - Jing Li; Yu Wang; Yujin Fu; Yizhong Chen (Environmental Pollution, 2025)

Investigation on the influence of the adjacent shoreline topography on harbor oscillations - Yujin Dong; Shixiao Fu; Bin Song; Leijian Song; Tongxiao Sun (Ocean Engineering, 2025)

A mixed layer height parameterization in a 3-D chemical transport model: Implications for gas and aerosol simulations - Hyeonmin Kim; Rokjin J. Park; Song-you Hong; Do-Hyeon Park; Sang-Woo Kim; Yujin J. Oak; Xu Feng; Haipeng Lin; Tzung-May Fu (Science of The Total Environment, 2024)

Synergistic effects of aluminum doping and amino functionalization to enhance adsorption capacity of ultrathin-nanosheet-assembled calcium silicate hydrate architectures for effective removal of Pb2+ and Cu2+ from aqueous solution - Yujin Xing; Shicheng Liu; Wenzhong Wang; Yujie Liang; Junli Fu; Qing Zhou; Lijuan Wang; Shimeng Huang (Journal of Environmental Chemical Engineering, 2024)

Study on photofluorescent uranium ore sorting based on deep learning - Jun Qiu; Yan Zhang; Chunqing Fu; Yuchao Yang; Yujin Ye; Renbo Wang; Bin Tang (Minerals Engineering, 2024)

Catalytic activation of percarbonate with synthesized carrollite for efficient decomposition of bisphenol S: Performance, degradation mechanism and toxicity assessment - Shicheng Liu; Sitong Liu; Huabin Chen; Yujin Xing; Wenzhong Wang; Lijuan Wang; Yujie Liang; Junli Fu; Chen Zhang (Journal of Hazardous Materials, 2024)

Mechanistic insights into efficient photocatalytic H2O2 production of 2D/2D g-C3N4/In2S3 photocatalyst by tracking charge flow direction - Huabin Chen; Yujin Xing; Shicheng Liu; Yujie Liang; Junli Fu; Lijuan Wang; Wenzhong Wang (Chemical Engineering Journal, 2023)

RETRACTED: Recent progresses, challenges, and opportunities of carbon-based materials applied in heavy metal polluted soil remediation - Tianhong Fu; Baige Zhang; Xing Gao; Shihao Cui; Chung-Yu Guan; Yujin Zhang; Bangxi Zhang; Yutao Peng (Science of The Total Environment, 2023)

Evaluation of Port–Hinterland Synergy Level Considering Fixed Asset Allocation and Social Commodity Circulation under the “Dual Circulation” Development Pattern - Zhaohui Li; Yujin Huang; Fan Yang; Yi Li; Yan Fang; Rui Fu (Journal of Marine Science and Engineering, 2022)
“Port–hinterland synergy” means the development of port and hinterland should promote each other. The “dual circulation” development pattern indicates the requirement of exploring the domestic transportation demand and promoting the integration between ports and hinterlands. However, the current research on the synergy level between ports and hinterlands is not enough to meet the needs of constructing a “dual circulation” development pattern, and few studies have explored the influencing factors of port–hinterland synergy level directly, especially in the context of the new development pattern of “dual circulation”. After investigating the synergetic mechanism between ports and hinterlands, this study proposes to further consider the influence of fixed assets allocation and social commodity circulation on the synergy level under the “dual circulation” pattern. So, fixed asset investment and three different forms of commodity circulation activities are selected to represent the corresponding hinterland’s economic activities and added into the evaluation indices. To assess ports’ responsiveness to different kinds of transport demand, throughputs of each port are divided into those of domestic and foreign countries. Then this paper evaluates the level of port–hinterland synergy by the coupling synergy model, and the influence degree of these activities on the synergy level was studied with the partial least squares regression (PLS). The results show that there is heterogeneity in regional and port positioning in the port–hinterland synergy level, and that four selected economic activities’ improvement can enhance the port–hinterland synergy level. Among them, retail industry has the strongest positive effect, followed by tertiary industry, import and export trade, and fixed asset investment.

The significance and variation characteristics of interlay water in smectite of hydrocarbon source rocks - JinGong Cai; LongFei Lu; YuJin Bao; Fu Fan; JinLi Xu (Science China Earth Sciences, 2012)